Integrating of Mobile Augmented Reality Applications Through Inquiry Learning to Improve Students’ Science Process Skills and Concept Mastery - Setiawaty, S.; Lukman, I. R.; Imanda, R.; Sudirman, S.; Rauzatuzzikrina, R. (Program Studi Pendidikan IPA Fakultas Matematika dan Ilmu Pengetahuan Alam (FMIPA), 2024)
Augmented reality (AR) is a transformational learning experience that can be used and integrated into science classes to overcome the shortcomings of conventional teaching. AR-enabled mobile apps have the potential to be used in blended/hybrid and face-to-face teaching, which is especially important during recovery from learning loss. This study aims to determine augmented reality as an educational medium in chemistry learning, which includes student acceptance of AR content in commercial mobile applications, improvement of learning outcomes, science process skills and mastery of student science concepts. AR media is developed through a 4-D procedure. Product test design is done by applying AR using quasi-experimental methods and receiving AR media through the TAM model. Data on N-gain scores for science process skills and mastery of chemistry concepts were collected through learning pretests and posttests, teacher and student learning observation activities, and teacher and student questionnaires to determine responses to the learning carried out. The results showed that most students found AR valuable and easy to use, had positive attitudes, and expressed an intention to use this educational technology if given the opportunity. Educational performance is highlighted because technical quality positively impacts perceived usefulness and ease of use. The use of AR in inquiry learning significantly influences improving students’ science process skills. Even though there are positive results, the use of AR in science still needs development because of the need for more helpful content and the different conditions of students.